Population Fluctuation and Damage Potential of Red Flour Beetle on Different Dry Fruits under Laboratory Conditions - Lubna Bashir Rajput; Arfan Ahmed Gilal; Aslam Bukero; Fida Hussain Magsi; Muhammad Ishaq Mastoi; Israr Mohi-ud-Din (Journal of Basic & Applied Sciences, 2016)
The study was conducted to determine the population fluctuation of red flour beetle Tribolium castaneum on different dry fruits under laboratory conditions from 6th March 2015 to 24th July 2015. Four different dry fruits viz; T1 (almonds), T2 (walnuts), T3 (peanuts), T4 (cashew nuts) and T5 (wheat as control) were used in the experiment. The standard weight of 50g of every dry fruit was kept in plastic jars and covered with muslin cloth. Ten pairs of beetles were released in each jar. Observations were recorded at fortnight interval and population of the live beetles was counted. Results of the study showed that the population of red flour beetles gradually increased in all the treatments control with respect to time. The highest overall mean population of T. castaneum was recorded in wheat (61.61±10.02) followed by cashew nuts (52.90±8.26), almonds (50.01±7.81) and walnuts (43.56±5.89). The lowest population of red flour beetles (27.41±8.26) was recorded in peanut. The highest weight loss was recorded in wheat (18.8 %), followed by cashew nuts (15.6%), almonds (14%), walnuts (11.2%) and peanuts (8%) respectively.